PERAN IBU DALAM KEGIATAN PENDAMPINGAN BELAJAR ANAK MELALUI PRINSIP INDIVIDUAL LEARNING-CENTERED - Abtokhi, Ahmad (EGALITA, 2009)
This research describing the role of the mother that very central in assisting children’s learning activities through the concept of mentoring that focuses on the uniqueness of each individual. This concept is termed a Learning- Centered Individuals who see uniquely child has potential, interests and dy- namics of each problem, so that the practical assistance should be focused on managing the potential and uniqueness of each individual dynamics prob- lems to deliver the right learning attitude, without forgetting the reaching academic achievement.Keywords: Ibu, pendampingan, belajar, Individual Learning-Centered